Application of Volumetric MR Spectroscopic Imaging for Localization of Neocortical Epilepsy - Maudsley, Andrew A. (2009)
PURPOSE: The aim of this study was to evaluate volumetric proton magnetic resonance spectroscopic imaging (MRSI) for localization of epileptogenic foci in neocortical epilepsy. METHODS: Twenty-five subjects reporting seizures considered to be of neocortical origin were recruited to take part in a 3-Tesla MR study that included high-resolution structural MRI and a whole-brain MRSI acquisition. Using a fully-automated MRSI processing protocol, maps for signal-intensity normalized N-Acetylaspartate (NAA), creatine, and choline were created, together with the relative volume fraction of grey-matter, white-matter, and CSF within each MRSI voxel. Analyses were performed using visual observation of the metabolite and metabolite ratio maps; voxel-based calculation of differences in these metabolite maps relative to normal controls; comparison of average grey- and white-matter metabolite values over each lobar volume; and examination of relative left-right asymmetry factors by brain region. RESULTS: Data from fourteen subjects were suitable for inclusion in the analysis. Eight subjects had MRI-visible pathologies that were associated with decreases in NAA/Creatine, which extended beyond the volume indicated by the MRI. Five subjects demonstrated no significant metabolic alterations using any of the analysis methods, and one subject had no findings on MRI or MRSI. CONCLUSIONS: This proof of principle study supports previous evidence that alterations of MR-detected brain metabolites can be detected in tissue areas affected by neocortical seizure activity, while additionally demonstrating advantages of the volumetric MRSI approach.